Pengembangan Media Pembelajaran Kimia Berbasis Komik Strip Digital untuk Meningkatkan Pemahaman Konseptual Siswa - Asmida Mariani; Gusnita Darmawati; Firdaus Annas; Yulifda Elin Yuspita (Intellect : Indonesian Journal of Learning and Technological Innovation, 2025)
Chemistry learning at MAN 2 Kota Payakumbuh is still predominantly conducted using lecture-based methods, which results in low student engagement and difficulties in understanding abstract concepts, particularly in atomic structure topics. This condition indicates the need for the development of innovative learning media that align with students’ learning characteristics. This study aims to develop digital strip comic–based learning media to enhance students’ conceptual understanding and learning motivation in Chemistry. The study employed a Research and Development (R&D) approach using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages, supported by the Luther–Sutopo multimedia development model. The research subjects included media experts, subject-matter experts, Chemistry teachers, and students at MAN 2 Kota Payakumbuh. Data were collected through validity, practicality, and effectiveness questionnaires. The results indicate that the developed digital strip comic learning media achieved a validity score of 0.76, a practicality score of 96.67, and an effectiveness score of 0.80, which fall within the high category. These findings demonstrate that digital strip comic–based learning media are feasible as an alternative instructional medium for Chemistry learning and are effective in improving students’ motivation and conceptual understanding of atomic concepts. The contribution of this study lies in providing empirical evidence for the development of visual narrative–based learning media to support Chemistry education at the secondary school level. Abstrak Pembelajaran Kimia di MAN 2 Kota Payakumbuh masih didominasi metode ceramah yang berdampak pada rendahnya keterlibatan siswa dan kesulitan dalam memahami konsep abstrak, khususnya pada materi struktur atom. Kondisi ini menunjukkan perlunya pengembangan media pembelajaran yang inovatif dan sesuai dengan karakteristik peserta didik. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis komik strip digital guna meningkatkan pemahaman konsep dan motivasi belajar siswa pada mata pelajaran Kimia. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan 4D yang meliputi tahap Define, Design, Develop, dan Disseminate, serta didukung oleh model pengembangan multimedia Luther–Sutopo. Subjek penelitian melibatkan ahli media, ahli materi, guru Kimia, dan siswa MAN 2 Kota Payakumbuh. Data dikumpulkan melalui angket validitas, praktikalitas, dan efektivitas. Hasil penelitian menunjukkan bahwa media pembelajaran komik strip digital memiliki tingkat validitas sebesar 0,76, tingkat praktikalitas sebesar 96,67, serta tingkat efektivitas sebesar 0,80 yang termasuk dalam kategori tinggi. Temuan ini menunjukkan bahwa media pembelajaran berbasis komik strip digital layak digunakan sebagai alternatif media pembelajaran Kimia dan efektif dalam meningkatkan motivasi serta pemahaman siswa terhadap konsep atom. Kontribusi penelitian ini terletak pada penyediaan bukti empiris pengembangan media pembelajaran berbasis visual naratif yang mendukung pembelajaran Kimia pada jenjang pendidikan menengah.